The Use of Raman Spectroscopy in Studying the Spectroscopy of Some Materials - Raghad Khaled Saab Rajaa; Rania Fadel Majeed Hussein; Duaa majeed kahdum odeha; Mohammed Khalid Hussien Ali (Genius Journals, 2024)
Raman spectra are considered one of the very important and necessary spectra, especially after the spread of technology and the development of science with wavelengths. Raman spectroscopy is considered one of the spectra that is difficult to obtain because its dispersion ratio is very small. This is one of the main obstacles to calculating Raman spectra.This research includes a study of the Raman spectra of the potassium tungstate and gadolinium KGW crystal in two ways. The first depends on the use of the OPO system, and the second depends on taking spectra in the traditional way using a Raman spectrometer. The results showed that there are clear differences in the characteristics of the Raman spectrum obtained by the two mentioned methods. When comparing these spectra with the reference spectra, the peaks were shifted from their positions and the large exposure of these peaks was revealed. The study also included the effect of the pumping direction on the characteristics of the Raman spectra of the crystal using Raman spectroscopy.
Keywords: Raman; Spectroscopy